2023
DOI: 10.1088/1402-4896/ace93f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manufacturing errors and micro-groove surfaces on the static and dynamic characteristics of water-lubricated bearings

Abstract: In this paper, the effects of manufacturing error and micro-groove on the static, dynamic and stability characteristics of water-lubricated journal bearings (WLJBs) are investigated. Mathematical expressions of manufacturing errors and surface micro-groove are presented, and the Reynolds equations with steady and unsteady states are calculated by using the linear perturbative method and the finite difference technology. According to the developed model, the effects of the waviness magnitude, spatial number, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Static and dynamic pressure thrust bearings offer numerous advantages, including robust axial loading capacity, high operational accuracy, exceptional vibration absorption performance and easy maintenance (Yu et al, 2017;Li et al, 2023a). Consequently, they are extensively used in various fields, including the automotive industry, precision machine tools and ocean engineering (Li et al, 2023b;Lu and Tian, 2023;Ueda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Static and dynamic pressure thrust bearings offer numerous advantages, including robust axial loading capacity, high operational accuracy, exceptional vibration absorption performance and easy maintenance (Yu et al, 2017;Li et al, 2023a). Consequently, they are extensively used in various fields, including the automotive industry, precision machine tools and ocean engineering (Li et al, 2023b;Lu and Tian, 2023;Ueda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [13] carried out singleside modification of eccentric sliding bearings and analyzed through numerical calculations to conclude that the reasonable design of single-side modification is beneficial to increase the minimum oil film thickness at the edge of the sliding bearing, reduce the rough contact, and improve the wear resistance. Li [14] established a hydrodynamic lubrication bearing model considering manufacturing errors and micro-grooves. The results indicated that an increase in the eccentricity ratio directly affected the variation of the bearing's static characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many scholars have conducted in-depth research in the fields of manufacturing errors and the lubrication of inclined bearings [5]. Li et al [6] studied the effects of manufacturing errors and micro grooves on the static, dynamic, and stability characteristics of water-lubricated radial bearings (WLJBs). The mathematical expressions for manufacturing errors and surface micro grooves were given, and the steady-state and non-stationary Reynolds equations were calculated using the linear perturbation method and the finite difference technique.…”
Section: Introductionmentioning
confidence: 99%